IMPERATIF ISLAM PROGRESIF: ANALISIS FILOSOFIS ATAS KEADILAN SOSIAL, KEADILAN GENDER, DAN HAK ASASI MANUSIA - Amantari, Riska Khofifah (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Abstract : The ideas formulated by progressive Islam, a trend in Islamic thought, to realize social justice, gender equity, and pluralism must awaken our humanity as part of the global human race, originating from the Prophet Adam (peace be upon him). This idea, regardless of background, ethnicity, religion, gender, or race, must be recognized. Progressive Muslims must fight all injustices around us. They must not only criticize injustices committed by Muslims themselves but also boldly criticize injustices perpetrated by the West. This is where the importance of the multiple critique initiated by progressive Islam becomes apparent. It encompasses various approaches to understanding Islamic tradition and modernity. This movement emphasizes a commitment to the values, practices, and goals of Islam, manifested in various ways. In this regard, it is important to highlight the reinterpretation of Islamic tradition using philosophical and historical approaches, examining the works of previous scholars with the thoughts of philosophers. Progressive thinkers strive to develop alternative interpretations appropriate to the modern era. Minority issues such as gender justice, human rights, and humanitarian justice are addressed. Gender justice is considered key to progressive Islam. Progressive thought also emphasizes the importance of human rights. Moosa highlights the differences between secular and Islamic human rights schemes, as well as the need for reconstruction within Islamic tradition. Progressive Muslim thinkers combine Islamic tradition with modern Western thought. They emphasize issues of social justice, gender, human rights, and harmony between Muslims and non-Muslims. Progressive Islamic studies involve textual sources and Islamic tradition. They act as intellectuals and are involved in the process of raising public awareness. Progressive Islam seeks to harmonize tradition and modernity to advance the understanding of Muslims. This movement is expected to have a positive impact on the development of Islamic society in contemporary debates. Keywords: Progressive Islam, Progressive Islamic Thought, Human Rights and Gender Justice